Effectiveness of Nitrate and Beta-Blocker Drugs in Patients with Angina Pectoris: A Systematic Literature Review - Maya Arfania; Adinda Khoirun Nissa; Khoirul Haniatin; Andriyani, Novita (HM Publisher, 2023)
Angina pectoris is the most common clinical manifestation of myocardial ischemia and often occurs when the heart needs more blood. The main goals of treatment in patients with unstable angina are relief of symptoms, slowing disease progression, and reducing future events, especially myocardial infarction, and death. This study aimed to explore the literature regarding the effectiveness of nitrate and beta-blocker drugs in angina pectoris patients. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding risk factors and clinical overview of acute kidney injury. The search was performed using the terms: (1)